On the Dynamics of a Cubic p-adic Polynomial - Mendes, S. (Nonlinear Maps and their Applications, 2014)
We investigate the dynamics of a cubic polynomial in the p-adic setting. Specifically, we describe the Siegel disks and the basin of attraction for the dynamical system using a result of Albeverio et al.